2010
DOI: 10.1057/emr.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Ownership concentration, family control and performance of firms

Abstract: This paper explores the relationship between firm performance, measured by Tobin's Q and very powerful controlling shareholders in a sample of Belgian listed firms. The paper shows that overall the largest shareholders have a negative effect on firm performance. Nevertheless, in family firms the effect of large controlling shareholders on performance is positive except when they are organized in voting blocks. Firms related to coordination centers display higher performance associated with large shareholders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
(41 reference statements)
3
22
0
4
Order By: Relevance
“…These firms are characterised by a strong (and often family-based) entrepreneurial imprint coupled sometimes with external management (Corbetta, 2000;Grundei and Talaulicar, 2002;Gabrielsson and Huse, 2005;Gabrielsson, 2007;Hamadi, 2010) that leads to a concentration of the executive power, which may in turn reduce the voluntary content of disclosure.…”
Section: Medium-sized Firms and Voluntary Disclosurementioning
confidence: 99%
“…These firms are characterised by a strong (and often family-based) entrepreneurial imprint coupled sometimes with external management (Corbetta, 2000;Grundei and Talaulicar, 2002;Gabrielsson and Huse, 2005;Gabrielsson, 2007;Hamadi, 2010) that leads to a concentration of the executive power, which may in turn reduce the voluntary content of disclosure.…”
Section: Medium-sized Firms and Voluntary Disclosurementioning
confidence: 99%
“…However, evidence regarding the performance implications of family ownership is mixed. Some studies find family ownership positively impacts firm performance (Anderson & Reeb, 2003;Barontini & Caprio, 2006;Hamadi, 2010;Maury, 2006;Singal & Singal, 2011). Other studies conclude that family ownership coincides with poorer firm performance (Bennedsen & Nielsen, 2010;Claessens, Djankov & Lang, 2000;Thomsen & Pedersen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Family ownership is used as an independent and moderating variable in several finance and corporate governance studies (e.g., Berrone, Cruz, Gomez-Mejia, & Larraza-Kintana, 2010;Hamadi, 2010;Villalonga & Amit, 2006). We found that 1.5% of the firms in our sample (97 firms) with family ownership had no family board members, no family chairman and no family CEO (see Table 3).…”
Section: Discussionmentioning
confidence: 76%